Fat from Tenebrionidae Bugs - Sterols Content, Fatty Acid Profiles, and Cardiovascular Risk Indexes - Jiri Mlcek; Anna Adamkova; Martin Adamek; Marie Borkovcova; Martina Bednarova; Ivana Knizkova (Polish Journal of Food and Nutrition Sciences)
This work focused on analysing the content of selected sterols and profile of fatty acids of edible insect species – mealworm ( Tenebrio molitor ) and superworm ( Zophobas morio ), which are expected to increase their usability in human nutrition. Sterols content was determined using capillary gas chromatography method. Cholesterol content was determined at 1335 mg/kg in dry matter (DM) for the mealworm, which was less than for superworm (3224 mg/kg DM). Other sterols analysed were stigmasterol and β-sitosterol, which were once again higher in superworm (stigmasterol – 44 mg/kg DM and β-sitosterol – 414 mg/kg DM) than in mealworm (stigmasterol – 18 mg/kg DM and β sitosterol – 171 mg/kg DM). From the nutritional point of view, the amount of cholecalciferol is also not negligible, which was 190 μg/kg DM in mealworm and 199 μg/kg DM in superworm. Atherogenic index (AI), thrombogenic index (TI), and cholesterol index (CSI) were calculated for both species and compared with the results of other authors. These indexes are often considered predictors of cardiovascular diseases. A potential benefit of both species could be the balanced proportion of sterols of animal and plant origin that could be nutritionally well-accessible and lower weight of dry matter necessary to consume to cover the daily dose of linoleic acid compared to dried beef.